Notes on krondirs, an interesting type of Late Medieval tin-and-lead vessels - Nikolay Markov (Приноси към българската археология, 2022)
The paper presents and analyses the earliest evidence available to date about a specific type of tin-andlead vessel used to store water and wine, and perhaps myrrh, known as “krondirs”. The conclusion is made that krondirs were most probably a product of Byzantine society, where they appeared as early as the Palaiologan Period. The hypothesis is rejected that the roots of this type of vessel lie in the East, in Central Asia, or even Egypt. The assumption is made that the centres where they were created were the Large Balkan Byzantine cities – Constantinople, Thessaloniki and Adrianople, from where their type not only spread, but in the early centuries of the Ottoman rule, their production blossomed to an extent.